Entre Cuidado e Exploração. Quando a Dívida Entra nas Relações de Família e Vizinhança num Bairro Periférico - Marie Kolling (Iberoamericana: Nordic Journal of Latin American and Caribbean Studies)
The proliferation of consumer credit during Brazil’s boom years was embedded in visions of national progress for all – including the very poor. This so-called “financial inclusion” has come at a high cost. Based on fieldwork in Salvador, Bahia (between 2012–2019), this article provides insights into the ways debt has transformed the conditions of urban poverty and social relations. In poor neighborhoods, families get caught up in vicious debt circles as they now struggle with a ‘double burden of debt’: debt in the local informal economy as well as the financialized economy. The ethnography shows that debt is often left unsettled, and that among women in a peripheral neighbourhood of Salvador, dreams and debt become intimately intertwined, as they depend on credit to provide for the family on a daily basis, to deal with unexpected events, and to “build a life” (construir uma vida). It is argued that in this context of stark poverty, debt fosters interdependencies that accentuate unequal and unstable relationships among neighbours and within families, relationships that are characterized by both care (Han 2012) and exploitation (Stack 1975). Resumo A expansão do acesso ao crédito para a população de baixa renda foi promovida como progresso nacional durante os anos de crescimento econômico no Brasil. Essa suposta “inclusão financeira” teve um custo alto. Baseado em trabalho de campo em Salvador, BA (entre 2012 e 2019), este artigo analisa como o endividamento está transformando as condições de pobreza urbana e as relações sociais. Nos bairros periféricos, as famílias se encontram presas em círculos viciosos de dívida, lutando com um ‘duplo fardo da dívida’: dívida na economia informal local, bem como na economia financeirizada. A etnografia mostra que, frequentemente, as dívidas não são liquidadas, e que para mulheres de um bairro periférico de Salvador, sonhos e dívidas se entrelaçam intimamente. Pois elas dependem do crédito para sustentar a família no dia a dia, para lidar com imprevistos, e para ‘construir uma vida’. Argumenta-se que nesse contexto de pobreza, a dívida fomenta interdependências que acentuam as relações desiguais e instáveis entre vizinhos e dentro das famílias, relações caracterizadas tanto pelo cuidado (Han 2012) quanto pela exploração (Stack 1975). Palavras-Chave: Dívida; Pobreza urbana; Vulnerabilidade; Financeirização